Evaluation of School-Based Health Education Intervention on the Incidence of Soil-Transmitted Helminths in Pupils of Rural Communities of Eastern Kogi State, North Central Nigeria - Clement Ameh Yaro; Ezekiel Kogi; Sodangi Abdulkarim Luka; Luay Alkazmi; Junaidu Kabir; Kenneth Nnamdi Opara; Gaber El-Saber Batiha; Kamba Bayo; Friday Maduka Chikezie; Albert Bamigbade Alabi; Salamat Ibrahim Yunusa (Journal of Parasitology Research)
The negative impact of soil-transmitted helminths (STHs) in Nigeria is enormous, and it poses serious public health issues and concerns. This study was undertaken to investigate the impact of health education intervention on reinfection of STHs in pupils of rural schools of Kogi East, North Central Nigeria. A total of 10 schools with the highest prevalence of STHs at baseline were selected from the 45 schools assessed during the baseline survey. These 10 schools were randomly paired into two groups of 5 schools per group. Five schools were dewormed and given health education (DHE) intervention while the other 5 schools were dewormed only (DO) without health education. Reassessment of schools for reinfection was carried out for a period of 12 months. Data obtained were analyzed using descriptive statistics. Student’s t-test was used to make comparison between interventions in the incidence of infections. Analysis was carried out at p<0.05. Reinfection with STHs was observed from the 28th week (7th month) of both interventions with incidence of 0.29 (2 pupils) and 1.00 (7 pupils) in DO and DHE schools, respectively. In the 36th week (9th month), incidence observed in schools given DHE was 0.56 (5 pupils) while incidence of 0.89 (8 pupils) was observed in DO schools, and there was no significant difference (t=−1.000, p=0.347) between the interventions. At 48th week (12th month), there was no significant difference (t=−0.547, p=0.599) in incidence between the DHE and DO schools with incidence of 1.00 (12 pupils) and 0.83 (10 pupils), respectively. Hookworms had an incidence of 0.78 (7 pupils) at DHE schools and 0.56 (5 pupils) at DO schools in the 36th week while an incidence of 0.92 (11 pupils) and 0.83 (10 pupils) at DHE and DO schools, respectively, in the 48th week. Ascaris lumbricoides was only observed in DHE schools in a pupil with an incidence of 0.11 (1 pupil) and 0.08 (1 pupil) at 36th and 48th weeks. There was no significant difference in the prevalence of the parasites between DO and DHE intervention groups (p>0.05). School-based health education intervention had no significant impact on STH incidence in pupils of rural schools in Kogi East. Community-based deworming should be encouraged alongside improvement in the water, sanitation, and hygiene infrastructures and practices at both school and home.